Visual Landscape Quality Assessment in Historical Cultural Landscape Areas - Keleş, Emine; Atik, Damla; Bayrak, Gökçen (European Journal of Sustainable Development, 2018)
Various factors such as rapid population increase, socio-economic changes and uncontrolled urbanization observed in cities caused many changes in urban areas. These changes damage natural and cultural landscape areas. It is observed that especially historical landscape areas couldn’t be protected as well as planning and management of these areas couldn’t be provided. Accordingly, constitution of inventory studies oriented natural, cultural and historical sources; presentation of planning and management decisions and arrangements that are integrated to historical identity and increasing environmental quality are steered. Visual Landscape Quality Assessment is one of the methods used in both our country and in the world for planning studies within the context of European Landscape Convention. The visual character of landscape consists of both natural-human made artifacts and physical-biological sources. The assessment includes a list of areas that are subject to cultural heritage conservation; it lends assistance for identifying various factors and preferences of physical landscape components. Edirne/Turkey is one of the most significant cities of the world being a cultural heritage area with its tangible and intangible cultural landscape elements. It is aimed to contribute to rational planning and conserving of cultural resources by preparing visual landscape quality assessment of Edirne city in this study. Keyword: Visual landscape quality assessment, historic cultural landscape, cultural heritage, cultural sustainability, Edirne